The Effect of 4C 5M Scientific Approach on Children's Memorization Achievement of Eighth Grade at MTs Tahfidz Yanbu'ul Qur'an Menawan Kudus - Maimun, Achmad Syafiq; Rohman, Fathur (International Journal of Islamic Thought and Humanities, 2025)
Tahfidz learning at MTs Pesantren Yanbu'ul Qur'an Menawan Kudus sets a target for eighth grade students to memorize 5 juz in one year as a condition for grade promotion. However, the achievement of santri memorization shows significant variations. Some students reach or exceed the target, while others are left behind. This study aims to analyze the effectiveness of the 4C 5M scientific approach on students' memorization achievement. This study used a correlative and quantitative approach, involving 153 8th-grade students as samples selected using the Simple Random Sampling technique. Data were obtained through memorization tests, questionnaires, and observations. The results showed that the 4C 5M Scientific approach contributed positively to the achievement of students' memorization, evidenced by the partial t-test results of 0.734> 0.05 and the determination of ability with R Square of 84.2%. Students who follow this method consistently improve memorization and quality of understanding. Therefore, this approach is recommended to improve students' memorization achievement in tahfidz educational institutions.